(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Promoting gender equality and empowering women continue to be crucial worldwide objectives, as emphasised by the United Nations’ Sustainable Development Goal 5 (SDG-5). Notwithstanding considerable advancements in tackling gender inequalities via worldwide, regional, and local efforts, women in India have always encountered severe obstacles originating from a patriarchal culture. Historical traditions such as sati, purdah, female foeticide, infanticide, dowry, and domestic abuse have effectively marginalised women. However, efforts have been made via constitutional and legal changes to address and overcome these problems. Recent decades have seen notable progress in women’s rights, driven by heightened awareness and lobbying, bolstered by many government initiatives targeting their empowerment. Nonetheless, deeply rooted patriarchal beliefs persist in perpetuating gender prejudice in both public and private domains. This paper presents an examination of the degrees of women’s empowerment in several states of India, using secondary data obtained from official sources. This paper examines the effects of female literacy on health and decision-making, the significance of government assistance via infrastructure and programmes, and the impact of women-focused organisations and self-help groups on economic empowerment. The results indicate that while there has been some improvement, continuous efforts are necessary to completely eliminate gender prejudice and improve women’s empowerment.